Organization and characterization of genetic regions in Bacillus subtilis subsp. krictiensis ATCC55079 associated with the biosynthesis of iturin and surfactin compounds - Kim, Young Tae; Park, Byung Keun; Kim, Sung Eun; Lee, Won Jung; Moon, Jae Sun; Cho, Min Seop; Park, Ho-Yong; Hwang, Ingyu; Kim, Sung Uk (PLOS ONE, 2017)
Bacillus subtilis subsp. krictiensis ATCC55079 produces the cyclic lipopeptide antibiotics iturin A–F as well as several surfactins. Here, we analyzed and characterized the biosynthetic genes associated with iturin and surfactin production in this strain. We aligned the sequences of each iturin and surfactin synthetase ORF obtained from a genomic library screen and next generation sequencing. The resulting 37,249-bp and 37,645-bp sequences associated with iturin and surfactin production, respectively, contained several ORFs that are predicted to encode proteins involved in iturin and surfactin biosynthesis. These ORFs showed higher sequence homologies with the respective iturin and surfactin synthetase genes of B. methylotrophicus CAU B946 than with those of B. subtilis RB14 and B. subtilis ATCC6633. Moreover, comparative analysis of the secondary metabolites produced by the wild-type and surfactin-less mutant (with a spectinomycin resistance cassette inserted into the srfAB gene within the putative surfactin gene region) strains demonstrated that the mutant strain showed significantly higher antifungal activity against Fusarium oxysporum than the wild-type strain. In addition, the wild-type strain-specific surfactin high performance liquid chromatography (HPLC) peaks were not observed in the surfactin-less mutant strain. In contrast, the iturin A peak detected by HPLC and liquid chromatography-mass spectrometry (LC/MS) in the surfactin-less mutant strain was 30% greater than that in the wild-type strain. These results suggested that the gene cluster we identified is involved in surfactin biosynthesis, and the biosynthetic pathways for iturin and surfactin in Bacillus strains producing both iturin and surfactin may utilize a common pathway.